The Effect of Guided Inquiry Assisted by Google Classroom on the Scientific Literacy at SMA Negeri 1 Kwanyar - Nurastuti, Galuh Yuli; Ibrohim, Ibrohim; Listyorini, Dwi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Scientific literacy is a crucial ability for work in the digital age. The aim of this study was to ascertain the impact of guided inquiry using Google Classroom on students' scientific literacy at SMA Negeri 1 Kwanyar. For the experimental class, which consisted of 104 students over 4 classes X MIPA, a pretest-posttest non-equivalent group design was adopted. A test for equivalency was used to choose the samples. The instruments used in this study are descriptive tests that make reference to scientific literacy indices. Analysis of covariance was used for the analysis (Anakova). The findings of this study show how guided inquiry using Google Classroom has